2021
DOI: 10.1111/1365-2664.13825
|View full text |Cite
|
Sign up to set email alerts
|

Legacy effect of grazing intensity mediates the bottom‐up controls of resource addition on soil food webs

Abstract: Large‐scale studies have demonstrated that nitrogen (N) and water (W) availabilities greatly affect terrestrial ecosystems world‐wide, and this is especially true for the resource‐poor semi‐arid grasslands. Yet, experimental evidence is lacking for how N and W availabilities affect soil food webs across historical grazing intensity‐altered environments at a local scale. Here, we included N‐ and W‐addition treatments in an 8‐year grazing experiment (with four grazing intensities) to determine how the legacy eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 81 publications
(111 reference statements)
0
12
2
Order By: Relevance
“…Plant species richness is an important indicator of the effectiveness of revegetation in degraded ecosystems (Devoto et al, 2012; Guiden et al, 2021). The substantial increase in plant species richness induced by short‐term revegetation in the current study is inconsistent with previous studies, which showed that revegetation did not alter species diversity or even reduced species diversity due to the limited availability of soil nutrients and water content in degraded grasslands (Wang et al, 2021; Wu et al, 2015; Wu et al, 2020). Our findings for plant productivity, species richness and community structure at both degradation intensities indicate that revegetation is effective for the restoration of degraded grasslands.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Plant species richness is an important indicator of the effectiveness of revegetation in degraded ecosystems (Devoto et al, 2012; Guiden et al, 2021). The substantial increase in plant species richness induced by short‐term revegetation in the current study is inconsistent with previous studies, which showed that revegetation did not alter species diversity or even reduced species diversity due to the limited availability of soil nutrients and water content in degraded grasslands (Wang et al, 2021; Wu et al, 2015; Wu et al, 2020). Our findings for plant productivity, species richness and community structure at both degradation intensities indicate that revegetation is effective for the restoration of degraded grasslands.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results do not support the ‘Field of Dreams Hypothesis’, which predicts that restoring plant diversity leads to the passive recovery of the biodiversity of other organisms (Devoto et al, 2012; Guiden et al, 2021). There are at least two possible explanations for the failure of revegetation to increase soil biodiversity in the current study: (a) at the outset of our study, the soil may have mainly contained soil organisms that are resistant to degradation stress and that are not altered by revegetation (Rousk et al, 2010; Wu et al, 2020; Xiao et al, 2020); and (b) the increases in plant diversity were insufficient to cause increases in the diversity of soil organisms (Scherber et al, 2010; Wang et al, 2021). Our VPA analyses confirmed that revegetation‐induced increases in soil bacterial and fungal biomass and changes in soil bacterial and fungal community structure were mostly associated with increases in plant variables (plant productivity and community structure).…”
Section: Discussionmentioning
confidence: 84%
“…This may be because the addition of N to the N‐limited systems directly increases the soil available N (Chen et al., 2019), which can be rapidly absorbed and utilized by plants, thus promoting plant growth and ecosystem productivity. Grazing, however, generally affects vegetation and soil through livestock feeding, trampling and excretion (Cingolani et al., 2005; Lemaire et al., 2000), so there may be an indirect lag effects on grassland (Wang et al., 2021). Previous studies have shown that grazing increases soil bulk density, decreases soil porosity and penetrability, and reduces soil nutrient and water availability (Eldridge et al., 2016; Shan et al., 2011), thus inhibiting plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the increase in the proportion of PP nematodes may be because the aboveground loss in lightly grazed ecosystems is lower compared to the underground compensation. At the same time, the increase in root biomass provides a parasitic habitat for PP nematodes, and the increase in root exudates provides an increase in food resources (Chen et al, 2013; Wang et al, 2021). Under moderate grazing conditions, the ratio of FF to OP nematodes in the surface soil layer increased, whereas the ratio of BF nematodes decreased.…”
Section: Discussionmentioning
confidence: 99%